2020
DOI: 10.1097/mao.0000000000002730
|View full text |Cite
|
Sign up to set email alerts
|

Tympanoplasty With or Without Balloon Eustachian Tuboplasty for Chronic Suppurative Otitis Media With Obstructive Eustachian Tube Dysfunction

Abstract: Objective: To further elucidate the role of balloon Eustachian tuboplasty (BET) in tympanoplasty, we conducted a study to compare the outcomes of tympanoplasty with and without BET for the treatment of chronic suppurative otitis media (CSOM) with obstructive Eustachian tube dysfunction (OETD). Study Design: Case control study. Setting: Tertiary referral center. Patients: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…As demonstrated by Chen S et al, at 12 months after the operation, the ABG an important indicator of hearing status [ 33 ] in children having otitis media with effusion treated with BET combined with myringotomy and Grommet insertion was smaller than those treated with myringotomy alone [ 34 ]. Moreover, the average ABG improvement was found in patients with CSOM and OETD treating with the combination of tympanoplasty and BET when compared with the control subjects enrolled for tympanoplasty [ 15 ], suggesting both Grommet insertion and BET could improve the hearing ability. In our study, the ABG was decreased obviously in the BET + Grommet group at 6 and 12 months after the surgery, and the postoperative ABG in the BET + Grommet group was better than that in the BET group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated by Chen S et al, at 12 months after the operation, the ABG an important indicator of hearing status [ 33 ] in children having otitis media with effusion treated with BET combined with myringotomy and Grommet insertion was smaller than those treated with myringotomy alone [ 34 ]. Moreover, the average ABG improvement was found in patients with CSOM and OETD treating with the combination of tympanoplasty and BET when compared with the control subjects enrolled for tympanoplasty [ 15 ], suggesting both Grommet insertion and BET could improve the hearing ability. In our study, the ABG was decreased obviously in the BET + Grommet group at 6 and 12 months after the surgery, and the postoperative ABG in the BET + Grommet group was better than that in the BET group.…”
Section: Discussionmentioning
confidence: 99%
“…All CSOM-ETD subjects fulfilled the following inclusion criteria: (1) The patients were diagnosed as CSOM, a perforated tympanic membrane with persistent drainage from the middle ear lasting >6∼12 weeks [ 20 ]; (2) Patients were identified as severe ETD according to the Eustachian Tube Dysfunction Questionnaire (ETDQ‐7, a seven‐question survey, Table 1 ) with the total score of ≥14.5 (mean score ≥2.1) and the symptoms lasting more than 3 months [ 15 , 21 ]. Exclusion criteria: (1) Patients had previously undergone treatment; (2) Patients were due for revision procedure; (3) Patients had a congenital ear anomaly, a history of ear surgery within the past 6 months, a history of head and neck cancer, acute otitis media, refractory chronic rhinosinusitis, recent use of ototoxic medications, or pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balloon dilation Eustachian tuboplasty has been used as an adjunctive procedure in the treatment of COM with ETD. 20 In our opinion, for patients with NPC having an inflamed ET, BET may provide some benefits in terms of clearing the mucociliary secretions of the middle ear to prevent such sequelae. The 2-stage operation or pre-CI surgery is necessary to achieve a safe and dry ear before CI.…”
Section: Restoration Of Etf and Middle Ear Cleft Functionmentioning
confidence: 90%
“…The rate of successful outcomes in this study was similar to those reported by previous studies of OETD [ 1 ]. A case-control study reported that patients who concurrently underwent BDET with tympanoplasty showed greater improvement in the air-bone gap than patients who underwent tympanoplasty without BDET (10.93±7.70 dB vs. 7.11±8.08 dB, P =0.033) [ 8 ]. Another prospective study reported favorable treatment outcomes of ETBD combined with cartilage tympanoplasty in patients with adhesive otitis media [ 9 ].…”
mentioning
confidence: 99%